Peran Orang Tua Dalam Menerapkan Home Schooling pada Pendidikan Anak Usia Dini - Noviansah, Ahmad; Sari, Buana; Priyadi, Maya Setia (Ibtida'iy : Jurnal Prodi PGMI, 2024)
Early childhood education (ECCE) is the level of education before the primary education level which is a coaching effort aimed at children from birth to the age of six years by providing educational stimulation to help physical and spiritual growth and development so that children have readiness to enter further education, which is held on formal, non-formal, and informal channels. Early childhood education is also functioned to build, process, and develop all the potential of children at an early age optimally so that basic behaviors and abilities that are in accordance with the level of development have readiness to enter further education. The research uses a library research approach or literary research. Library Research is a type of qualitative research that generally does not go into the field in finding data sources. This study aims to find out how the implementation model of home schooling, home schooling methods and approaches, the benefits of home schooling, and the advantages and disadvantages of home schooling.